329 Prolonged Use of Narcotic Following Lumbar Spine Surgery: Predictive Factors and Outcome Analysis. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Chieng, Lee Onn; Madhavan, Karthik; Teferi, Nahom T; Wang, Michael Y; Vanni, Steven
Abstract: INTRODUCTION: Opioid crisis has recently been declared as a public health emergency in the United States. Patients underwent lumbar spine surgery often receive narcotic to control acute postoperative. In our study, we aim to study whether prolonged use of postoperative narcotic affects surgical outcome. METHODS: A retrospective review of prospectively maintained institutional lumbar spine database was conducted. Basic demographic and outcome data at 3 and 12 mo postop were obtained. We defined prolonged use of narcotic as more than 2 wk of its usage. Multivariate analysis was utilized in this study. RESULTS: A total of 328 patients were included in our analysis. Of these 29% (n = 94) had prolonged use of narcotic postoperatively. There were no major differences in basic demographic characteristics (age, sex, ethnicity, insurance) between 2 groups. Those who received prolonged narcotic medications tend to consume narcotic preoperatively (60.6% vs 48.3%, P  = .043) and underwent spinal fusion (70.2% vs 48.7%, P  = .001). In regard to discharge disposition, there were high rate discharges to home with home health setting (14.9% vs 7.7%) in those receiving prolonged course of narcotic, but interestingly low rate of discharge to postacute care setting (8.5% vs 11.1%). Undoubtedly, there were higher readmission rate at 30 d (7.4% vs 4.7%, P  = .008) and 3 mo postop (8.5% vs 4.3%, P  = .037). CONCLUSION: We concluded that prolonged use of narcotic was associated with worse clinical outcome following surgery. A solution to reduce narcotic dependence post lumbar spine surgery is desperately needed.